Performance multidisciplinar nas ações de pesquisa, desenvolvimento e capacitação: produção de materiais didáticos hipermidiáticos no Moodle - Jacques, Juliana Sales (2014)
This study investigated the performance of the Multidisciplinary Team of the Open University of Brazil (UAB) at the Federal University of Santa Maria (UFSM), concerning the actions of research, development and training for the production of hypermediatic didactic materials on the Moodle. The objectives are as listed: track and record the actions in the orientation process of the didactic materials preparation on the Moodle; update the Perfo_List indicators form as a methodology for the retrospective and prospective actions in the team; program a subject on the Moodle in order to exemplify the hypermediatic resources associated to the study activities; and elaborate indicators of pedagogical orientation to the hypermediatic structuring of resources and study activities in the virtual environment. An action research was developed, in order to achieve the proposed objectives, establishing cyclic planning stages, implementation, evaluation and replanning of the actions that pervade the development of hypermediatic didactic materials. The action research strategies were supported by the propositions of three mediator matrices: the Dialogical-Problem Posing Matrix (DPM), the Theme-Organizer Matrix (TOM) and the Theme-Analytical Matrix (TAM), which respectively guided the data collection, organization and analysis. The research instruments (diary of participant observations and survey questionnaires) were steered by the sixteen questions of the DPM and by the Perfo_List form indicators. Therefore, the action research is structured in five chapters, reasoned by the Freirean concept of Dialogical Problem-Posing Education, the Actor-Network Theory and the Study Activity Theory. In the light of the analytical categories elected (technological and pedagogical innovation and collaborative interaction), the research action results, which are sustained by data triangulation, indicate that the multidisciplinary performance enhances the integration of hypermedia in the development of didactic materials. Thus, actions of research, development and training, guided by the collaborative interaction of the team, generate technological and pedagogical innovation that boosts the teaching and learning mediated by network technologies.